New species and records of the genus Extraordinarius Rheims, 2019 (Araneae: Sparassidae: Sparianthinae) - Rheims, Cristina A. (Zootaxa, 2022)
In this paper, I revisit the genus Extraordinarius Rheims. I describe the female of E. klausmeinei Rheims and two new species: E. alicecooperi spec. nov. (♂♀) from Espírito Santo and E. angusyoungi spec. nov. (♀) from Rio de Janeiro, all in southeastern Brazil. In addition, I include an identification key for all species of the genus, a new record for E. brucedickinsoni Rheims and an updated distribution map for the genus.